Valuation of 2-wheel tractors for Life Cycle Assessment analysis : technical report - Martinez Perez, Gabriel; Loon, Jelle J. van (EiA, 2023)
This report is part of a collaboration between the Autonomous University of Chapingo (Mexico) and CIMMYT for the mechanization work related with Advances Research Institute (ARIs). The objective of this collaboration is focused on performing a life cycle assessment analysis of a two-wheel tractor compared to animal drawn equipment. The present report describes the progress of this collaboration including the 2-wheel tractor disassembly to analyze and cost the complete manufacturing process (methods, materials, and resources). For this, computer-aided design (CAD) software SolidWorks© was used for creating accurate 3D models of each piece of the tractor, facilitating a detailed visualization of the geometry and operations required for construction. Additionally, to promote capacity building, two training workshops to students were conducted by CIMMYT focused on the development of prototypes of sustainable machinery from a smallholder perspective and the use of SolidWorks software packages for virtual sketching and 3D engineering.